Constitution and Sustainable Development - (:unkn) unknown (ISTANBUL UNIV, FAC LAW, 2020)
In the legal framework, sustainable development as a concept was firstly used and elaborated upon in international law. The concept has generally been treated as a matter of soft law by international instruments. However there is also non-negligible number of hard law documents that regulate specific elements of sustainable development. The concept had begun to find its place in the constitutions by the late 1980's. In fact, the issues that the concept of sustainable development refers to were already regulated by national constitutions. However, the concept of sustainable development brought up a meaning different to that which was regulated by the constitution before. Sustainable development changes the way people relate to other people, society and the state. This shift can be observed by analysing the rights, duties and obligations that the concept imposes. This shift caused a transformative effect on constitutionalism's old model of relationships based entirely on the state-individual dichotomy. This dichotomy functions when the primordial aim of constitutionalism is considered as the limitation of government authority for the protection of constitutional rights of the individuals. However the function of constitutionalism is no longer limited to this unequal relationship. The concept reconstructs and diversifies the functions of constitutionalism by perpetuating the conception of common survival in the planet. This conception requires more responsible citizens and much more responsible enterprises. The state is no longer the sole debtor of the constitution. Sustainable development imposes a privatization of constitutional relations. Despite the absence of the concept in the wording of the Turkish Constitution of 1982, Constitution refers systematically to the three pillars of sustainable development. The Constitution envisaged development plans as to the effective realisation and integration of the three pillars of sustainability.
Keywords: Constitution; Sustainable development; Soft law; Environment; Social justice; Economic development; Intergenerational justice; Intra-Generational justice; Solidarity